Heat pumps for cold climate heating : variable volume ratio two-stage vapor compression air source heat pump technology and applications - Huang, Hui (Boca Raton : CRC Press, Taylor & Francis Group, 2020)
Air source heat pumps are mainly used for space heating, and have the advantages of environmental protection, energy saving, and comfort. Written by a leading heat pump technology expert, this book summarizes the research and applications of variable volume ratio two-stage vapor compression air source heat pump technology, and its use in cold climate regions. This book can be used for reference by scientific researchers and engineers engaged in research on air source heat pump technology, product development and popularization; and by energy management and policy researchers. It will also be of value to undergraduate and graduate students studying these areas of technology.
Introduction. Analysis of Variable Volume Ratio Two-stage Compression Heat Pump Cycle. Triple-cylinder Two-stage Compressor with Variable Volume Ratio. Basic Principles of System Control. Optimization Analysis of Low Temperature Air Source Heat Pump System. Low Temperature Air-to-Air Source Heat Pump. Low Temperature Air-to-Water Heat Pump. Bibliography. Index.
OCLC-licensed vendor bibliographic record.
Keywords: TECHNOLOGY / Engineering / Mechanical; Air source heat pump systems